PENERAPAN PROGRAM INTENSIFIKASI SISTEM MINA PADI (INSISMINDI) PADA KELOMPOK TANI DI DESA SUNGAI BAKAR KECAMATAN BAJUIN KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Yarna Hasiani; Fitri Mahyudi; Husinsyah (Fakultas Pertanian UVAYA Banjarmasin, 2025)
implementation of mina padi on agricultural land is carried out by maintaining fish between rice plants in the fields that utilize the puddles of rice fields as a place for fish cultivation. The existence of this maintenance system makes rice plants and fish experience mutualistic symbiosis. Where rice gets natural fertilizer from fish waste and fish food waste, and gets protection from fish from rice plant pests. Meanwhile, fish use rice plants as a place of protection against predators and get natural food from rice pests. The mina padi system in rice fields is still rarely found, this is due to the lack of information about the mina padi system so that farmers have not implemented it in rice fields. Based on the conditions above, the role of changing the mindset of rice farmer groups from a monoculture system to INSISMINDI is a challenge and opportunity to increase farmer income, especially partner farmer groups. From the cultivation activities of plants with the intensification of the rice-fish system that has been implemented, it can be concluded as follows: Cultivation of plants with the intensification of the rice-fish system can increase plant production, because this rice-fish planting system provides benefits including: (a) Soil fertility can be increased, (b) Weed growth can be suppressed, (c) the population of pests and diseases of rice plants can be suppressed, (d) Fish behavior in searching for food can improve soil structure. With the rice-fish planting system, land efficiency and productivity increase by 35% compared to cultivation without rice-fish (monoculture).